Exploring the status of the vulnerable guiña (Leopardus guigna) in Patagonia, Argentina - Agostini, Ilaria (2024)
The guiña (Leopardus guigna), the smallest felid in the Neotropics, is distributed along a narrow strip of Valdivian and Andean Patagonian forests of Chile and Argentina. Most of the information about the guiña comes from studies carried out in Chile, but very little is known about this rare and threatened species in Argentina, except for a few scattered records. To assess the status of a population of guiñas, we carried out the first large-scale camera-trap survey, locating 80 camera-trap stations over an area of 590 km2 in the second largest protected area of Argentina, the Nahuel Huapi National Park, in northwestern Patagonia. From November 2022 to April 2023, over 3395 camera-trap days, we detected guiñas at four sites. The species was recorded in lenga beech, coihue beech and Valdivian forests, and in proximity to vehicular dirt roads or along a hiking trail. These few records suggest that the guiña is rare in this area. Large protected areas of northwestern Patagonia may play an important role in protecting small populations of this felid in Argentina.